Isolasi, Identifikasi, dan Aktivitas Antibakteri Fungi Endofit Daun Jarak Pagar (Jatropha Curcas L) Terhadap Klebsiella pneumoniae dan Streptococcus pneumoniae - Wardani, Dea (STIKes Ibnu Sina Ajibarang, 2024)
Jatropha curcas (Jatropha Curcas L) is a plant that has been widely used by the public to treat various diseases and has antibacterial power. This cannot be separated from the secondary metabolite content it contains. The presence of endophytic microbes in these plants makes them interesting to study. This study aimed to determine the number of endophytic fungal isolates and the antibacterial activity of endophytic fungal isolates from Jatropha leaves against Klebsiella pneumoniae and Streptococcus pneumoiae. The test methods of this research are isolation and purification of endophytic fungi and identification of bacteria-producing endophytic fungi of jatropha leaves, as well as testing the diameter of the inhibitory zone of endophytic fungi of jatropha leaves against Klebsiella pneumoniae and Streptococcus pneumoniae using the agar diffusion method using paper disks. The results of the research obtained 9 isolates which were suspected to be Chaetomium sp DJPT 1, Fusarium sp DJPT 2. Gliocladium sp DJPT 3, Aspergillus fumigatus DJPT 4, Geotrichum sp DJPT 5, Aspergillus niger DJPM 1, Cladosporium sp DJPM 2, Beauveria bassiana DJPM 3, and Aspergillus flavus DJPM 466. Endophytic fungal isolates from Jatropha leaves have antibacterial activity against the growth of Klebsiella pneumoniae and streptococcus pneumoniae.